2017
DOI: 10.1002/lary.26929
|View full text |Cite
|
Sign up to set email alerts
|

Developing a synchronous otolaryngology telemedicine Clinic: Prospective study to assess fidelity and diagnostic concordance

Abstract: 2c. Laryngoscope, 128:1068-1074, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 16 publications
2
91
0
2
Order By: Relevance
“…Using VNG for remote screening has previously been proposed by Newman‐Toker et al, who have suggested using recorded oculomotor exams in the emergency department for the diagnosis of stroke and acute dizziness using video head impulse testing goggles . Furthermore, synchronous otolaryngology telemedical visits have previously been shown to be effective as well as cost‐effective, including in the field of neuro‐otology . Still, most prior studies on tele‐otolaryngology describe using specialized and costly equipment, which limits the practicality of widespread adoption in today's cost‐conscious environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using VNG for remote screening has previously been proposed by Newman‐Toker et al, who have suggested using recorded oculomotor exams in the emergency department for the diagnosis of stroke and acute dizziness using video head impulse testing goggles . Furthermore, synchronous otolaryngology telemedical visits have previously been shown to be effective as well as cost‐effective, including in the field of neuro‐otology . Still, most prior studies on tele‐otolaryngology describe using specialized and costly equipment, which limits the practicality of widespread adoption in today's cost‐conscious environment.…”
Section: Discussionmentioning
confidence: 99%
“…Still, BPPV is often diagnosed via oculography; thus, we believe 30 patients prove feasibility. In similar studies, Newman‐Toker et al utilized a sample size of 12 patients, Yulzari et al utilized 48 patients to assess teleotolaryngology consults, and Seim et al utilized 21 patients to evaluate synchronous visits . Additionally, the nature of the nystagmus elicited by BPPV is that the response fatigues with repetition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these are relatively recent studies, we would argue that in our current circumstances, rhinologic patients are amenable to consultation on a remote basis as well. Additionally, there are already available telemedicine platforms used in Otolaryngology that demonstrate its potential benefits in evaluating patients in remote and underserved areas [6], such as Quintree (Quintree Medical LLC, Detroit, Michigan, USA).…”
Section: Telemedicinementioning
confidence: 99%